2012
DOI: 10.1097/coc.0b013e3182610537
|View full text |Cite
|
Sign up to set email alerts
|

ACR Appropriateness Criteria® Definitive Therapy for Early-Stage Cervical Cancer

Abstract: This manuscript represents the consensus opinion of an expert panel based on a survey of all available medical literature. This manuscript may be used to inform the clinical decision making of physicians involved in the treatment of early-stage cervical cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 53 publications
0
18
0
1
Order By: Relevance
“…(Pecorelli et al, 2009) However, its utility is low in guiding adjuvant therapy (Hricak et al, 2005). Although clinicopathologic factors have been suggested to guide postoperative adjuvant therapy selection, controversy surrounding the independence of these factors for prognosis of cervical cancer patients still exists (Chang et al, 2009;Small et al, 2012). These different results may be due to the heterogeneity of the population enrolled in different studies (Kamura et al, 1992;Yuan et al, 1998;Ho et al, 2004;Singh et al, 2012).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…(Pecorelli et al, 2009) However, its utility is low in guiding adjuvant therapy (Hricak et al, 2005). Although clinicopathologic factors have been suggested to guide postoperative adjuvant therapy selection, controversy surrounding the independence of these factors for prognosis of cervical cancer patients still exists (Chang et al, 2009;Small et al, 2012). These different results may be due to the heterogeneity of the population enrolled in different studies (Kamura et al, 1992;Yuan et al, 1998;Ho et al, 2004;Singh et al, 2012).…”
Section: Discussionmentioning
confidence: 57%
“…Although NCCN (Grochola et al, 2008)guidelines have suggested that adjuvant therapy should be applied to certain patients with intermediate or high risk factors after surgery, these factors remain controversial in many studies (Kamura et al, 1992;Yuan et al, 1998;Creasman and Kohler, 2004;Ho et al, 2004;Chang et al, 2009;Singh et al, 2012;Williams et al, 2015). Therefore, different opinions on the impact of prognostic factors between studies may lead to various selection criteria for adjuvant therapy, as suggested by researchers (Chang et al, 2009;Small et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, the investigators of a prospective trial showed that 18 F‐FDG PET/CT had a minimal effect on preoperative decisions regarding local disease . Elsewhere, CT was shown to have only modest sensitivity and specificity in diagnosing parametrial invasion …”
Section: Introductionmentioning
confidence: 99%
“…18 Elsewhere, CT was shown to have only modest sensitivity and specificity in diagnosing parametrial invasion. 19 This study is a retrospective description of the management of the patients with cervical cancer in one single institution based on the physical examination, high-detail TVS, and 18 F-FDG PET/CT, in the decision triage of patients with cervical cancer to surgery or chemoradiation therapy. For the purpose of this study, the final histology of the surgical specimens was compared with the results of the TVS and 18 F-FDG PET/CT to assess the contribution of these imaging modalities to the treatment decision.…”
Section: Introductionmentioning
confidence: 99%
“…This information is of great value for practitioners in choosing appropriate imaging modalities for the assessment of cervical cancers and endometrial cancers (27)(28)(29).…”
Section: Pet/ct Imagingmentioning
confidence: 99%